Trichloroisocyanuric Acid as an Efficient Reagent for the Synthesis of Phosphoroamidates via Atherton–Todd Reaction under Base-Free Conditions - Kaboudin, Babak; Donyavi, Atousa; Kazemi, Foad (Synthesis, 2018)
A simple, efficient, and novel method is developed for the synthesis of phosphoroamidates via an Atherton–Todd coupling reaction of amines with dialkyl H-phosphite using trichloroisocyanuric acid as an efficient and safe reagent. Treatment of amines with dialkyl H-phosphite and trichloroisocyanuric acid under base-free conditions gives phosphoroamidates in moderate to good yields. The reaction proceeded effectively to afford the corresponding phosphoroamidates via a dehydrogenative coupling of H-phosphonates with amines. This method is easy, rapid, and good-yielding for the synthesis of phosphoroamidates.
Keywords: phosphoroamidate; amines; dialkyl H-phosphite; coupling; Atherton–Todd reaction